Global, Regional, and National Age-sex-specific Mortality and Life Expectancy, 1950–2017: A Systematic Analysis for the Global Burden of Disease Study 2017 - Feigin, V; GBD 2017 Mortality Collaborators (Elsevier, 2018)
No abstract.